Magnetic metal phenolic networks: expanding the application of a promising nanoprobe to phosphoproteomics research. Issue 76 (25th August 2020) - Chu, Huimin; Zheng, Haoyang; Yao, Jizong; Sun, Nianrong; Yan, Guoquan; Deng, Chunhui
Abstract : Ti–tannic acid modified Fe3 O4 was prepared through a facile, mild and eco-friendly synthesis procedure and can be applied to identify phosphopeptides from HeLa cell extracts with high efficiency. Abstract : A Ti–tannic acid modified magnetic nanoprobe was synthesized via one step, and applied to phosphopeptide extraction. 3456 phosphopeptides and 1285 phosphoproteins were finally identified from 100 μg HeLa cell extracts. This opens up a new avenue for metal phenolic networks in phosphoproteomics research.